The Economic Impacts of Minimum Wage Laws: A New Look at an Old Question - Linneman, Peter (Journal of Political Economy, 1982)
This article uses a radically different methodology to address the question of the impact of minimum wage laws on employment and earnings. The methodology uses the adult wage structure which exists prior to a change in the federal minimum wage to identify the members of the subminimum wage population. This allows the parameterization of the disemployment effects of the minimum wage amendment on the subminimum population and the spillover employment effects on the above-minimum population. The members of the subminimum population are found to experience considerably reduced employment probabilities and annual hours worked (conditional on employment). Some evidence of above-minimum spillover effects is also found. The paper evaluates the impact of the minimum on the earnings distribution and concludes that the burden of the minimum wage falls most severely on females. This effect on adult females is surprisingly neutral with respect to race. The greatest beneficiaries of the minimum among the adult population are union members. Once again, this effect is relatively neutral with respect to race.